Association between women’s empowerment and contraceptive failure in Indonesia: 2017 IDHS data analysis - Sizi Lia Ginoga; Omas Bulan Samosir; Triasih Djutaharta (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Contraceptive failure has negative consequences, including unwanted pregnancies and abortions, which can cause maternal morbidity and mortality. Contraceptive failure is influenced by individual factors such as the user and the quality of the contraceptive method/device. One of the individual factors is the cultural factor which can be seen from the empowerment of women in improving the quality of health, including the use of contraception. There is no study which has discussed women’s empowerment as the determination of contraceptive failure. Purpose: Therefore, this study aims to analyze the association of women’s empowerment in contraception failure in Indonesia. Methods: The data source used is the results of the 2017 IDHS (Indonesia’s Demographic and Health Survey) with the unit of analysis from the period of using contraceptives to women who get pregnant while using contraceptives. The dependent variable is the duration of contraceptive usage. The main independent variable is women’s empowerment as measured by four indicators, namely asset ownership in the name of the wife, ability of decision-making in the household, ability to earn cash by working, and attending at least junior high school. Data were analyzed using the survival analysis method. Results: The results of the analysis show that the four factors of women’s empowerment have a significant negative association with contraceptive failure after controlling for socioeconomic, demographic, and environmental factors. Conclusion: Variables that are positively associated with contraceptive failure are participation in household decisions, education, residence status, and internet usage. Variables that are negatively associated with contraceptive failure are asset ownership, working status, and number of children.